A randomized, double-blind, placebo-controlled, proof-of-concept trial of creatine monohydrate as adjunctive treatment for bipolar depression - Toniolo, Ricardo Alexandre (J Neural Transm (Vienna), 2017)
Depressive episodes are a major cause of morbidity and dysfunction in individuals suffering from bipolar disorder. Currently available treatments for this condition have limited efficacy and new therapeutic options are needed. Extensive research in the pathophysiology of bipolar disorder points to the existence of mitochondrial and bioenergetic dysfunction. We hypothesized that creatine monohydrate, a nutraceutical that works as a mitochondrial modulator, would be effective as an adjunctive therapy for bipolar depression. We conducted a double-blind trial in which 35 patients with bipolar disorder type I or II in a depressive episode by DSM-IV criteria and in use of regular medication for the treatment of this phase of the disease were randomly allocated into two adjunctive treatment groups for 6 weeks: creatine monohydrate 6 g daily (N = 17) or placebo (N = 18). Primary efficacy was assessed by the change in the Montgomery–Åsberg Depression Rating Scale (MADRS). We did not find a statistically significant difference in the comparison between groups for the change in score on the MADRS after 6 weeks in an intention-to-treat (ITT) analysis (p = 0.560; Cohen’s d = 0.231). However, we found significant superiority of creatine add-on vs. placebo when we considered the remission criterion of a MADRS score ≤ 12 at week 6 analyzing the outcome of the 35 randomized patients on ITT (52.9% remission in the creatine group vs. 11.1% remission in the placebo group) and of the 23 completers (66.7% remission in the creatine group vs. 18.2% remission in the placebo group) (p = 0.012; OR = 9.0 and p = 0.036; OR = 9.0, respectively). Two patients who received creatine switched to hypomania/mania early in the trial. No clinically relevant physical side-effects were reported or observed. This proof-of-concept study, aiming to restore brain bioenergetics using an adjunctive mitochondrial modulator, is not conclusive on the efficacy of creatine add-on for bipolar depression, but suggests that this compound may have a role in the adjunctive treatment of this phase of the illness. Further investigation through randomized controlled trials with larger samples should be conducted to verify the efficacy of creatine supplementation for bipolar depression and also for subsyndromal depressive symptoms.